Polio vaccination campaigns in conflicts: succeeding while other humanitarian efforts fail? - Sabahelzain, Majdi M.; Agha, Hazem; Davidovitch, Nadav; Razum, Oliver (Frontiers in Public Health, 2025)
In conflict settings, public health interventions such as vaccination campaigns and improvements in water, sanitation, and hygiene (WASH) could benefit all parties involved. However, while polio vaccination campaigns frequently succeed in securing humanitarian pauses, WASH initiatives attempting to improve safe water supply and sewage disposal rarely achieve the same outcome. Using the Israel-Gaza conflict as an example, we analyze the factors contributing to the success of polio vaccination campaigns compared to WASH initiatives. We identify four key elements that facilitate the implementation of polio campaigns in conflict zones: (i) the ubiquitous decline in vaccine coverage and the subsequent detection of polio cases; (ii) international institutional support, including the role of the Global Polio Eradication Initiative (GPEI); (iii) the shortness of the required humanitarian pauses, the vertical nature, and the straightforward impact assessment of vaccination campaigns; and (iv) their “neutral” character due to an intentionally restrictive focus on children as the primary beneficiaries. Although polio vaccination campaigns do not typically lead to lasting peace and WASH initiatives often fail to secure even temporary humanitarian pauses, public health efforts should seize every opportunity to foster cooperation between warring parties. Such initiatives can help build trust, laying the groundwork for future peace negotiations and post-conflict reconstruction.